Mini Economica Media Komunikasi Ilmu Ekonomi : Pengaruh Strategi Diversifikasi Terhadap Manajemen Laba, dengan Faktor Moderasi Struktur Kepemilikan pada Perusahaan di Indonesia Periode 2008-2013 - Hakim, Luqman (Fakultas Ekonomi dan Bisnis Universitas Indones, 2015)
The purpose of this study is to determine the impact of diversification strategies on the earning managements. This study use structure ownership consisting of family and institutional ownership as moderating factors of the relationship between diversification strategy on the earning management. Consistent with transparency hypothesis, the study find that diversification provides the needed context for this accounting practice to be possible.